Jet Formation Mechanism of the Gamma-Ray-emitting Narrow-line Seyfert 1 Galaxies. (1st September 2022) - Chen, Yongyun; Gu, Qiusheng; Fan, Junhui; Yu, Xiaoling; Xiong, Dingrong; Ding, Nan; Guo, Xiaotong; Ge, Xue
Abstract: We use a large sample of gamma-ray narrow-line Seyfert 1 galaxies ( γ -NLS1s) to study the jet formation mechanisms. We find that the jet power of γ -NLS1s is lower than the maximum jet power of the Blandford–Payne (BP) mechanism. At the same time, we find that there is a significant correlation between jet power and accretion disk luminosity. Moreover, the contribution rates of the accretion to the jet power are larger than that of black hole mass to jet power. These results further suggest that the jet of γ NLS1s is mainly produced by the BP mechanism.